2009
DOI: 10.5694/j.1326-5377.2009.tb02815.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost is a major barrier to the use of inhaled corticosteroids for obstructive lung disease

Abstract: Objective: To examine the effect of the level of patient copayment on the rate of purchase of inhaled corticosteroids (ICS) by patients with obstructive lung disease. Design and setting: Cross‐sectional study of records of all prescriptions for ICS dispensed to general and concessional beneficiaries aged 15 years or over in the period January 2003 to December 2006. Data were obtained from the Pharmaceutical Benefits Scheme, which subsidises medication costs for all Australians. Main outcome measures: The numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…At the time of the surveys, NZ patients paid a dispensing fee of USD 2.48 for 1 month's supply of each prescription item, compared with the copayment in AU of USD 5.98 for concession card holders and USD 36.51 for the remaining one‐third of participants. Higher patient copayment is known to be a significant contributor to poor adherence, independent of socio‐economic status …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of the surveys, NZ patients paid a dispensing fee of USD 2.48 for 1 month's supply of each prescription item, compared with the copayment in AU of USD 5.98 for concession card holders and USD 36.51 for the remaining one‐third of participants. Higher patient copayment is known to be a significant contributor to poor adherence, independent of socio‐economic status …”
Section: Discussionmentioning
confidence: 99%
“…Higher patient copayment is known to be a significant contributor to poor adherence, independent of socio-economic status. 27,28 In assessing the implications of these findings, the higher cost to payers of ICS/LABA than ICS-alone should also be considered. In a US study of mild asthma, direct asthma-related costs were 34% higher if treatment was initiated with ICS/LABA compared with ICS-alone.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that patient copayments, a feature of the Australian Pharmaceutical Benefits Scheme, cause financial concern 2,17 and may influence prescription acquisition and use for some Australians. [3][4][5]18 Given the higher co-payments of the general beneficiary group (AU$ 31.30 per item at the time of the survey), it might have been expected that cost was of greater importance to this group. However, cost was mostly not discussed during consultations, and for all three cost questions, higher proportions of concession card holders reported it to be an important consideration.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In Australia, there is evidence that costs impact differently on prescription medicine use by general beneficiaries and concession card holders. 2,5 Most research in this field has addressed the affordability of medicines covered by insurance programmes. But at its core, the policy of charging patients is not simply about sharing costs.…”
mentioning
confidence: 99%
“…In particular, patients with reversible airflow obstruction, eosinophilic inflammation, 13 severe airflow obstruction and frequent exacerbations gain significant benefits from regular inhaled corticosteroid use 14 , 15 . Research at the Australian Centre for Asthma Monitoring has shown that people who purchase inhaled corticosteroids at the concessional Pharmaceutical Benefits Scheme price are dispensed 2.5 times more prescriptions for these medications than those who pay the full (general beneficiary) price 16 . While some of this difference may indicate unnecessary or excessive use, it is clear that a scheme that makes drugs from this class available at a reduced price to those who are most likely to benefit from them and cannot currently afford them will result in substantial health gains.…”
mentioning
confidence: 99%